A Suspicious Skin Lesion: Sufferings of A Remittance Warrior - Reza, Ishrat Binte; Ahasan, HAM Nazmul; Prince, SM Kawser Zafor (Journal of Medicine, 2023)
Tuberculosis verrucosa cutis (TVC) is a rare form of cutaneous tuberculosis. it is usually found as a solitary lesion but Extensive multifocal presentation is very rare. Here, we report this case of extensive, multifocal tuberculosis verrucosa cutis in a 36-year-old immunocompetent male patient in the absence of any primary tubercular focus. J MEDICINE 2023; 24: 67-68